Produksi dan Kapasitas Tampung Padang Pengembalaan di Desa Sejaro Sakti Kecamatan Indralaya Kabupaten Ogan Ilir - Muhakka, Muhakka; Munawar, Asep Indra; Fariani, Armina; Sahara, Eli; Sabrina, Salmi (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2024)
Muhakka, M., Ali, A. I. M., Riswandi, R., Fariani, A., Sahara, E., & Sabrina, S. (2024).Production and carrying capacity of pasture in Sejaro Sakti Village, Indralaya District, Ogan Ilir Regency. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-12 Tahun 2024, Palembang 21 Oktober 2024. (pp. 501–511). Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Forage is very important to increase ruminant livestock production. The purpose of this study was to determine the production and carrying capacity of pasture in Sejaro Sakti Village, Indralaya District. This study was conducted in the pasture area in Sejaro Sakti Village, Indralaya District, and at the Animal Nutrition and Feed Laboratory of the Animal Husbandry Study Program, Faculty of Agriculture, Sriwijaya University. The method used in this study was the Halls method, which took samples using a 1m2 sample plot to determine the type and production of forage. The parameters observed were the vegetation types in the swamp pasture, fresh weight production, dry matter production and carrying capacity. The results of the study showed 9 types of swamp green vegetation, namely Kumpai minyak grass (Hymenache amplexicausis), Kumpai padi (Oryza rupifogon), Purun tikus (Eleocharis dulcis), Algae (Spirogyra sp.), Eceng Gondok (Eichornia crassipes), Kiambang (Salvinia cucullata), Telepuk padi (Nymphanea adorate), Serpang (Caesalpinia sp.) and Kemon air (Neptunia oleracea). Fresh production of swamp greens is 1.10 tons Ha-1 and dry matter production is 0.23 tons.Ha-1 and carrying capacity is 0.66 AU.Ha-1.year-1. It can be concluded that the fresh production of swamp greens in the pasture in Sejaro Sakti Village is 1.10 tons.Ha-1 and dry matter production is 0.23 tons.Ha-1 and carrying capacity is 0.66 AU.Ha-1.year-1.